Green Carbon Part 2. The role of natural forests in carbon storage - Berry, Sandra (ANU Press, 2010)
This report is the second in a series that examines the role of natural forests and woodlands in the storage of carbon. Understanding the role of natural ecosystems in carbon storage is an important part of solving the climate change problem. This report presents a landscape-wide green carbon account of the 'Great Western Woodlands' (GWW), sixteen million hectares of mostly contiguous natural woody vegetation to the east of the wheatbelt in south-western Western Australia. For the first time, we provide an overview of the vegetation structure, climate, geology and historical land use of the GWW, and examine how these interact to affect the carbon dynamics of this region's landscape ecosystems. An analysis of time-series of satellite imagery is used to develop a fire history of the GWW since the 1970s. These layers of environmental information, along with field survey data and remotely sensed greenness, are used to construct a spatial model to estimate biomass carbon stocks of the woodlands at the present day, and to infer an upper limit to the carbon sequestration potential of the GWW. A range of management options to enable protection of high quality carbon stocks and restoration of degraded stocks are evaluated.